Mechanical characterization of AA6061-T6 aluminum alloy friction stir and tungsten arc welded with and without post-weld heat treatment - Fadaeifard, Firouz (2016)
Friction stir welding (FSW) process is a solid-state method in which is accepted as a favorable joining method for aluminum alloys and other engineering materials. The joining of metal plates in FSW is done at below their melting point temperature and based on a thermo-mechanical action used by a non-consumable welding tool onto metal plates. Despite the fast development in solid state welding, fusing welding such as Tungsten Inert Gas welding (TIG) is still vastly applied for thick joint design. Furthermore, solid state joining such as FSW is not applicable for positions such as overhead, horizontal and vertical. On the other hand, aluminum alloys have been increasingly applied in different industries, therefore, several research works on the manufacturing processes of these alloys have been developed over the time such as joining (welding) processes. The 6061-T6 aluminum alloy is an Al-Mg-Si precipitation hardening alloy from the 6XXX series which is often employed because it presents relatively good mechanical properties in relation to its light weight. Since the microstructure of 6061-T6 aluminium alloy and chemistry as well as dimension and distribution of the intermetallic particles in the matrix of aluminium alloy may be changed owing to heat generated and severe plastic deformation during the welding process. Accordingly, mechanical properties of weldments can be changed after welding as opposed to the base metal. However, the vast part of these changing can be recovered by doing post weld heat treatment (PWHT). Butt joints of 6061-T6 aluminum alloy were produced by FSW, and the influence of process parameters on their welds quality of weldments in terms of welding defects, microstructure, hardness distribution, and tensile properties by applying the shoulder angle and welding speed in the range of 0-10° and 63-110 mm/min, respectively, have been investigated using NDT, optical microscopy, scanning electron microscopy (SEM) equipped with energy dispersive x-ray (EDX) facilities, XRD, Electron backscatter diffraction (EBSD) and mechanical test such as microhardness test and the tensile test on the welded joints, as the first and second objective. The welding results obtained shown that among all the welding conditions, two welding parameters which is 10°– 89 mm/min and 10°-110 mm/min showed the highest tensile properties (184 MPa for UTS) and higher hardness. Consequently, one of them selected to perform post weld heat treatment (PWHT). In additional to above mentioned characterization, nanoindentation test was done to find local mechanical and nanomechanical properties in as-weld and PWHT of selected sample (as stated in third objective). The majority of properties were closed to the base metal condition by performing PWHT. The TIG welding process was performed on 60061-T6 aluminum alloy using ER5356 filler. All above mentioned characterization was performed to find mechanical and nanomechanical properties in as-weld and PWHT conditions. PWHT led to microstructural recovery of the Heat Affected Zone (HAZ) in addition to the appearance of β-phase (Al3Mg2) in the grain boundaries of weld zone. The ultimate tensile stress was improved to 204 MPa, even though the improvement in FSW sample (after PWHT) was better with almost 300 MPa. Final comparison between the effect of these two process on mechanical, metallurgical and nanomechanical properties of 6061-T6 aluminum alloy as well as the effect of PWHT in the properties studied shows better mechanical, metallurgical and metallurgical properties.